Novel computerized halal pharmaceuticals supply chain framework for warehouse and procurement - Raja Ikram, Raja Rina; Mohd Khanapi, Abd Ghani; Hasan Basari, Abd Samad (Foundation Of Computer Science (FCS), 2013)
Computerized systems and software technology are extensively used to enhance manufacturing and supply chain performance in the pharmaceutical industry. The halal pharmaceuticals industry is growing and more study is required to cater this evolving industry as technology progresses and advanced computerized systems are introduced in the manufacturing sector to increase productivity. Enforcement and religious authorities require a documented guideline to enforce halal certification whenever a manual operation is substituted by a computerized system. The current halal pharmaceuticals certification guidelines by enforcement agencies in Malaysia and Indonesia mainly focus on manual operations. This paper shall propose a framework to manage the halal supply chain when computerized systems are being used for the warehouse and procurement module. The proposed framework is the outcome of a case study of a Malaysian pharmaceutical organization, Pharmaniaga Manufacturing Berhad in Bangi, Selangor.